Correlation of Wisconsin glacial events between the Eastern Great Lakes and the St. Lawrence Lowlands - Dreimanis, A. (Géographie physique et Quaternaire, 1977)
The interrelationship of the Wisconsin glaciogenic events among the Upper St. Lawrence Lowland and the eastern Great Lakes, particularly the Lake Ontario basin is controlled mainly by 3 factors: 1) presence or absence of a glacial dam across the St. Lawrence Lowland; 2) isostatic lowering or rise of the outlet of Lake Ontario, related mainly to glacial loading or unloading in the Upper St. Lawrence Lowland; 3) shifting in the regional direction of glacial movement through the Upper St. Lawrence Lowland, upglacier from it, and in the Lake Ontario basin. Changes in the above conditions result in detectable changes in lake levels, and in compositional changes of tills in the Lake Ontario basin. Crosschecking of the above relationships supports the relative sequence already proposed. However, the chronology of the events which are older than reliable finite 14C dates, may be reinterpreted by a comparison with oceanic stratigraphies. A possible re-interpretation of some late-glacial Late Wisconsin glacial fluctuations depends greatly upon the reliability of 14C dates on shells and correct interpretation of till-like deposits. For those glacial fluctuations in the St. Lawrence Lowlands which lack 14C dates, it is tempting to apply correlations with the 14C dated stratigraphie units of the Great Lakes Region, but we have to consider also possible regional differences in glacial dynamics.